Isokinetic ankle muscle strength is reduced in recreational runners with medial tibial stress syndrome and is not associated with pain - Roger Andrey Carvalho Jardim; Renan Lima Monteiro; Cleuton Braga Landre; Maycon Sousa Pegorari; Natália Camargo Rodrigues Iosimuta; Areolino Pena Matos (Universidade Estadual Paulista (UNESP), 2022)
Abstract Aim: The purpose of this study was to investigate the strength and ratios of the plantar flexors and ankle dorsiflexors in recreational runners with medial tibial stress syndrome and to assess the association between muscle strength and the level of pain in this population. Methods: Two groups (control and medial tibial stress syndrome) of eighteen runners each participated in this cross-sectional study. Isokinetic dynamometry was used to evaluate muscle strength, and for the analysis, the normalized isokinetic peak torque controlled by gender was used. Results: The medial tibial stress syndrome group showed lower normalized isokinetic peak torque in the dorsiflexors in the concentric (p = 0.008) eccentric (p = 0.011) contraction, as well as a lower plantar flexor, normalized isokinetic peak torque in the concentric (p = 0.001) and eccentric (p = 0.02) when compared to the control group. However, there was no difference in the normalized isokinetic peak torque ratio representative of the stance (p = 0.62) and swing phase (p = 0.16), and the level of pain was not correlated with the strength concentric (p = 0.32) and eccentric (p = 0.621) of plantar flexors, nor to the concentric (p = 0.21) and eccentric of dorsiflexors (p = 0.54). Conclusion: Recreational runners with MTSS showed decreased muscle strength in the sagittal plane of the ankle, no correlation with the level of pain, and no changing the ratio between plantar flexors and dorsiflexors.